Nickel-Catalyzed Highly Atom-Economical C–C Coupling Reactions with π Components - Xiao, Li-Jun; Ye, Meng-Chun; Zhou, Qi-Lin (Synlett, 2019)
This account describes our latest advances in the field of nickel(0)-catalyzed hydrofunctionalization of π components. All reactions proceed either through internal hydride transfer or by using an external proton as the hydride source, thereby eliminating the use of stoichiometric amounts of reductants or oxidants. These nickel-catalyzed atom-economical coupling reactions demonstrate that nickel not only is an inexpensive metal catalyst, but also possesses unique and versatile catalytic abilities. Current limitations and the outlook of these reactions are also discussed.1 Introduction2 Nickel(0)-Catalyzed Hydroacylation of Styrenes with Simple Aldehydes3 Nickel(0)-Catalyzed Hydroalkenylation of Imines and Aldehydes with Alkenes4 Nickel(0)-Catalyzed Hydroarylation of Styrenes and 1,3-Dienes with Organoboronic Derivatives5 Nickel(0)-Catalyzed Hydroalkylation of 1,3-Dienes with Simple Ketones6 Summary and Outlook
Keywords: alkenes; ketones; nickel; aldehydes; imines; coupling